Assessment of Different Strategies in Optimizing Network Operation Incorporating PV System - Zen L. Chai; S.P Ang; A. Khalil; M. A. Salam; William Voon (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2019)
Renewable distributed generation is increasingly deployed in distribution networks for meeting the rapidly-growing electricity demand and energy transition target. Its optimal integration could maximize the benefits in network operation and eliminate technical challenges to passive networks associated with its non-dispatchable generation characteristic. In this paper, various scenarios based on three different optimization strategies viz. i) distributed installation, ii) power factor and iii) network configuration are assessed. The optimization goals are minimizing active line losses and improving network voltage profile within the constraints. The analysis considers PV system integration, and the base configuration of centralized PV system installation is taken as the reference for comparison. Time-series load flow algorithm utilizing average PV system generation and load demand profiles is adopted in solving the multi-objective optimization problem with index weighting factors. A real 11 kV distribution network in Brunei is modeled as the test system and integrated with the scenario-based PV system. The variations in generation and demand are considered in the work. The findings present the opportunities in furthering network operation enhancement with the distributed installation strategy having the highest potential. The analysis provides a clear optimization potential of each scenario, which shall be beneficial to the utility in planning new deployment.